KEMAMPUAN TEKNIK PEMAKAI MEMODERASI PENGARUH EFEKTIVITAS SISTEM INFORMASI AKUNTANSI PADA KINERJA INDIVIDUAL KOPERASI SIMPAN PINJAM - Mahendra, I Gede Aditya; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi; Vol 15 No 3 (2016), 2016)
This study aimed to test the effectiveness effect of accounting information system on individual performance and to determine the technical capabilities of users in moderating influence on the accounting information system effectiveness in the performance of individual credit unions in the district of Tabanan. This study was conducted in 24 credit unions in the district of Tabanan. Samples in this study of 66 respondents to the sampling technique used was purposive sampling. The data collection method used is the method of questionnaires. The data analysis technique used is the technique of analysis Moderating Regression Analysis (MRA). The findings of this study prove that the variable effectiveness of accounting information systems positive effect on individual performance. This study also gives the result that the variable user technical ability to moderate the influence of the effectiveness of the system of accounting information on the performance of individual credit unions in the district of Tabanan.
Keywords: User Engineering capability, effectiveness of SIA, Individual Performance